PENGARUH PENAMBAHAN POLIFOSFAT DAN NATRIUM KLORIDA TERHADAP PENINGKATAN DAYA IKAT AIR UDANG PUTIH BEKU DAN EFISIENSI PROSES - Azis Boing Sitanggang; Andrian Teguh; Adil Basuki Ahza (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
White shrimp (Litopanaeus vannamei) is one of the most popular seafood commodities, therefore, it has considerable economic value. The aim of this study was to evaluate the effect of polyphosphate and sodium chloride addition in the soaking solution on the water holding capacity (WHC) of frozen white shrimp at a pilot scale (i.e. 12 kg), production cost efficiency and its sensory acceptance. Various combina-tions of salt and phosphates concentration were evaluated to obtain the most optimum condition for in-creasing the frozen shrimp WHC while the final product phosphate residue did not exceed 0.5%. The highest WHC was obtained by soaking the white shrimps in a solution containing 2.5% polyphosphate MTR 80-P and 1.0% NaCl. The phosphate residue concentration determined in the final product was about 0.27%. The final product multisample difference test (rating test) also confirmed that this combination was not detrimental to the perception of the consumers. Moreover, the use of soaking condition reduced the production cost (based on the raw material costs) by Rp. 4.580,900/2.000 kg finished products or equals to Rp. 2.290/kg finished products. Conclusively, the addition of polyphosphate and salt in soaking solution at the optimum concentration increased the WHC of the frozen white shrimps, reduced production cost without changing the product sensory acceptance.